Improving Mobile Telephone Helplines for Effective Emergency Responses in Nigeria (Global Journal of Human-Social Science, 2021)
Communication technologies have in reality reshaped and redefined how things are done in the contemporary world. On daily basis, technologies are made easier to access and use, especially in times of emergencies. This study examines how mobile phones can be used to quickly obtain assistance for people in times of emergencies like accidents, natural disasters, as well as terrorist attacks. In advance countries where these technologies are in use; they adopt cheaper and easy to operate, special phone numbers are reserved for quick responses by care-givers to address sudden emergency occurrences. This study extensively examined the operations of National Emergency Management Agency (NEMA) and all its subsidiaries, and provide practical suggestions on how these emergency care-givers can adopt the use of mobile phone based technologies for more improved and quicker emergency response time. These include among others, provision of special code number, ensuring lines are accessible anytime for 24 hour and must be toll free access.
Keywords: emergency; mobile; helpline; response; emergency response; GSM